Ioanikyi Galyatovskyi translated by Samujil Bakačyč: reception and transformation - Stoianova, Daryna (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2025)
This article is dedicated to the study of translational transformations in the narratives about Marian miracles from “Key of Understanding” by I. Galyatovskyi and adapted to the Serbian-Bulgarian linguistic and cultural context. The translator, Samujil Bakačyč Bakačić, integrates Galyatovskyi’s stories into his translation of the anthologe “Miracles of the Theotokos” by the Greek author Agapios Landos. The research is based on an analysis of Bakačyč’s Venetian autograph (second half of the 17th century, National Library of St. Mark, Venice, cataloged as No. 297) and I. Galyatovskyi’s 1659 book “Key of Understanding”. It has been emphasized that the nature and specifics of lexical, lexico-grammatical, grammatical, and stylistic translational transformations demonstrate Bakačyč’s effort to faithfully, accurately, and adequately convey the original text’s content. At the same time, they reveal his deliberate attempt to adapt the text for an ethnically distinct but genetically related audience. The study highlights that, at times, the translator’s role evolves into that of a co-author. It is noted that the translation process neutralizes Galyatovskyi’s strong orientation toward the vernacular, replacing the vivid linguistic features of 17th-century Ukrainian with linguistic units characteristic of the classical church language. Although Samuil Bakačyč does not explicitly indicate the source of his additions to Landos’s of narratives, the dissemination of the anthological collection “Miracles of the Theotokos” in the Balkan-Slavic region contributed to the integration of Galyatovskyi’s works into the literary process of South Slavic nations.